Nutritional ergogenic resources in sport: lights and shadows on their use (Research, Society and Development, 2022)
The reliability of the use of ergogenic nutritional resources in the performance and health of the athlete still seems to have not reached a consensus among specialists in the field. Improper prescription and lack of consumer information have raised concerns about the use of this resource in relation to what it promises to offer and the adverse events that manifest themselves. This study deals with a narrative review of the reading on the use of nutritional ergogenic resources by athletes. The article is structured on a critical and reflective analysis of the literature, mediated by a traditional literature review. The selection of articles, reviewed and classified as support for writing, was arbitrary and interfered with the subjective perception of the authors, as allowed by the chosen study method. The information was obtained by searching the database of Academic Google, Pubmed, SciELO, Lilacs and Medline. The descriptors used were: nutritional ergogenics and supplementation AND yield. Special care is expected when choosing ergogenic supplementation, especially those related to the volume and intensity of effort. The proposals for sports nutrition plans inserted in the athletic environment are valid for possible clarification, discrimination of the use of nutritional ergogenic resources and individualized action on the consumer, in addition to ongoing programs for health promotion and disease prevention, helping to guide the choices adopted by athletes and how to ensure that the benefits outweigh the possible negative side effects.